IAA as a microbial activator for enhanced low-temperature nitrogen removal: mechanistic insights and pilot-scale validation - Zihan Su; Jihang Liu; Xiaotong Cui; Liang Fu; Bin Cui; Dandan Zhou (Water Research, 2027)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

High-performance Ti3C2-mediated adsorptive membrane for selective lithium recovery from shale gas wastewater - Dandan Zhao; Feiyang Yuan; Yuchun Ren; Yan Li; Keji Zhou; Xiaoying Huang; Chen Fu; Zhengjun Gong (Desalination, 2026)

How grazing intensity modulates precipitation driven processes of soil moisture, nutrients, and microbially mediated carbon cycling in a desert steppe - Xu Li; Wenling Fu; Yang Chen; Dandan Chen; Xin Li; Xiaoqian Li; Tianming Gao; Jianying Guo; Xinchuang Chen; Yiqun Ren; Zhi Dong (CATENA, 2026)

Extrusion-induced structural reorganization of starch-ca HMB complexes for modulating starch digestibility and controlling nutrient release - Dandan Wang; Lulu Li; Yifan Fu; Ling Xin; Huili Tong; Dong Liang; Qingmin Kong; Na Zhang; Xiaofei Liu (Food Research International, 2026)

Synergistic electrocatalytic reduction-oxidation cascade for efficient degradation of triclosan over an optimal amino-ionic liquid functionalized CoNi/RGO cathode - Dandan Xu; Xueli Xie; Han Zhou; Qin Zhang; Yanan Zhang; Min Huang; Yijian Zhong; Mingming Fu; Shaoyuan Bai (Environmental Research, 2026)

Retraction notice to “Surfactant enhances anaerobic fermentative hydrogen sulfide production: Changes in sulfur-containing organics structure and microbial community” [Sci. Total Environ. 880 (2023) 163025] - Xuemei Li; Qizi Fu; Wenming Wang; Xuran Liu; Dandan He; Xiaomei Jiang; Qiliang Yang; Dongbo Wang (Science of The Total Environment, 2026)

Effect of five selected flavonoids on the stability of anthocyanins: Kinetics, structural characterization, and interactional characteristics - Yini Fu; Yafei Dong; Jifang Miao; Xiaojuan Fan; DanDan Li; Yixuan Chen; Xingqian Ye; Yanyun Zhu (Food Chemistry, 2026)

Occupant-centric air conditioning control: Fusing multi-modal sensing and probabilistic model prediction - Wanyue Chen; Shengze Lu; Yan Ding; Dandan Yu; Jihui Yuan; Shaohui Chu; Sujuan Fu (Building and Environment, 2026)

Loss of CmMAIL2 compromises chloroplast function but permits developmental progression in melon - Liting Fu; Kexin Chen; Dongyang Dai; Kaihong Hu; Yuxuan Ma; Dandan Li; Yupeng Pan; Hanqiang Liu; Yunyan Sheng (Plant Science, 2026)

High-throughput sequencing and metabolomics reveal changes in microorganisms, volatile metabolites, and free fatty acids in preceding and after the 4th round stacked fermentation of sauce-flavored Baijiu - Shaoji Zhang; Yao Lin; Tianxiang Wu; Dandan Yuan; Shoufa Jiang; Ping Fu (Food Chemistry, 2026)

Hydrogeochemical and hydrogeological controls on spatiotemporal dynamics of groundwater phosphorus in a Lake Basin - Ying Zhu; Guangcai Wang; Fu Liao; Hairu Mao; Zheming Shi; Pengpeng Zhou; Bai Gao; Xiaodong Chu; Xianglong Chen; Zhiyuan Qiao; Yuanyuan Liu; Dandan Huang; et al. (Journal of Hydrology, 2026)

Green synthesis of glycine from CO2 via multi-enzyme cascades immobilized on HOF and COF carriers - Hongling Shi; Muran Fu; Jiaojiao Li; Xueyang Bai; Feifei Sun; Dandan Li; Yunchao Kan; Lunguang Yao; Cunduo Tang (Journal of Environmental Chemical Engineering, 2026)

A deprotection-oxidation cascade-regulated dual-responsive near-infrared fluorescent probe for individual and sequential detection of H2S/HClO with applications in food safety monitoring - Jie Yang; Chao Fu; Yicong Zhou; Hua Zhang; Xiangzhi Song; Dandan Li; Chuanxiang Liu (Analytica Chimica Acta, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

The hazards and resource utilization of construction and demolition waste - Yanan Zhang; Bensen Xian; Chenchen Liao; Ruifang Lu; Wenkai Sun; Mei Wang; Shaoyuan Bai; Qin Zhang; Huili Liu; Dandan Xu; Mingming Fu (Journal of Environmental Management, 2026)

Vanillin-derived bio-based Schiff base for simultaneously enhancing flame retardancy, crystallizability and UV-shielding of poly(L-lactic acid) - Mengmeng Wei; Leihua Jia; Dandan Fu; Zhenhua Shi; Masrina Mohd Nadzir; Junsheng Wang; Yipaerguli Yiminniyazi; Li Fan; Qiran Wang; Fude Liu; Bo Wang; Jinjun Yang (Chemical Engineering Journal, 2026)

Review of Sargassum thunbergii (Fucales, Phaeophyta): phycology, chemistry, bioactivity, and application - Xueyu Wang; Dandan Xiao; In-Kyu Yeo; Lei Wang; Yiqiao Li; Jia Fu; Yunhua Fu; Suengmok Cho; You-Jin Jeon; Fengqi Yang (Algae, 2025)
Sargassum thunbergii is a large brown seaweed endemic to the Northwest of Pacific Ocean, widely distributed in the warm temperate coastal waters of South Korea, China, and Japan. It is abundant in resources and has a long history of application, widely used in food, medicine, and feed. In recent years, it has also been used to restore marine ecology. To date, only one review has been published on Sargassum thunbergii aquaculture. Therefore, by investigating the international definitive data repository (ScienceDirect, PubMed, Web of Science, ACS Publications, Springer, etc.) and collecting 92 kinds of literature closely related to phycology, chemistry, biological activity, and applications, herewith a comprehensive and systematic summary and exposition, enveloping the classification and distribution, botanical characteristics, and physiological and biochemical differences of Sargassum thunbergii ; involving 7 chemical classifications of 117 derivatives substances embracing 12 new and 6 first-isolated excluding polysaccharides; mainly including 11 types of pharmacology in vivo and in vitro; evaluating the potential applications related on medicine, healthcare, aquaculture, and marine restoration. This review is expected to provide forward-looking scientific perspectives and act as a valuable reference for future studies, development, and utilization of Sargassum thunbergii .

V-ATPase B mediates Bt Cry1Ac binding and toxicity in Grapholita molesta - Dandan Pan; Jiayang Feng; Jiacheng Ye; Xiaoyan Yang; Xiaoyan Zhang; Xiaofang Sha; Donghan Wang; Yanshen Fu; Chunxiao Men; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

Transcriptome and physiological analysis revealed core genes that promote glutathione metabolism in blue honeysuckle in response to freezing stress - Yuxin Fan; Dandan Zang; Tianyi Wang; Zhihua Song; Na Li; Hongyan Cao; Tingting Du; Meng Qi; Yujie Fu; Qing Yang; Biying Dong; Dong Meng (Tree Genetics & Genomes, 2025)

ATP synthase subunit γ mediates Cry1Ac binding and toxicity in Grapholita molesta - Jiayang Feng; Dandan Pan; Yichen Wang; Xiaoyan Zhang; Xiaofang Sha; Yanshen Fu; Jiacheng Ye; Donghan Wang; Xiangqun Yuan; Yiping Li (Pesticide Biochemistry and Physiology, 2025)

Suppression of Fe loss to promote reconstructed surface via black phosphorus over NiFeB nanosheets for efficient water oxidation - Zehao Wang; Huayu Chen; Yesheng Fu; Hang Yin; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Wei Gao; Da Chen; Yang Hou (Chemical Engineering Journal, 2025)

Modified carboxymethyl cellulose for simultaneously enhancing fire-proofing, crystallizability, UV-barrier and hydrophilicity performances of bio-based poly(L-lactic acid) - Zhenhua Shi; Mengmeng Wei; Tong Gao; Dandan Fu; Masrina Mohd Nadzir; Junsheng Wang; Leihua Jia; Wenjiao Yuan; Bo Wang; Jinjun Yang (Chemical Engineering Journal, 2025)

Ortho-N-S/N-O dual-site synergistic COF for efficient selective removal and highly sensitive detection of hydrated lead ions - Huizhen Sun; Xiuhua Chen; Zongdeng Wu; Wenhui Ma; Shaoyuan Li; Chen Li; Dandan Wu; Kaixin Fu; Kexiang Ding (Chemical Engineering Journal, 2025)

Self-assembled Fe-HTO/MXene/PSF lithium ion-sieve membrane for efficient lithium extraction from shale gas wastewater - Yuchun Ren; Dandan Zhao; How Yong Ng; Chen Fu; Yuan Liu; Yongsheng Fu; Zhenglian Wu (Water Research, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Achieving all-weather efficient steam generation by designing scalable multi-layered fabric system - Dandan Zhong; Yunhe Wang; Mengyao Cai; Jianhong Guo; Leyan Zhang; Jiajing Zhang; Junyao Gong; Qiang Zeng; Chunhua Zhang; Zhuan Fu; Liangjun Xia (Chemical Engineering Journal, 2025)

Plant Heme-Binding Proteins: Insights into Functions and Application Prospect - Yao Sun; Yao Li; Guoqing Huang; Qiong Wu; Xin Sun; Jiaying Xue; Di Fu; Dandan Wang; Lei Wang (Plant Molecular Biology Reporter, 2025)

Selection of microRNA expression reference genes for RT-qPCR in poplar root under low nitrogen stress - Chun Wang; Tiantian Fu; Zeqi Wang; Jiahao Liu; Siyu Hou; Yiyi Yin; Xiaoqian Yang; Dandan Xiao; Yanwei Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Near-complete mineralization of sulfamethoxazole through intimately coupled Fe2O3/Mn2O3-catalytic ozonation and biodegradation with low ozone dosage - Shaozhu Fu; Simin Tao; Chongjun Zhang; Dandan Zhou (Journal of Cleaner Production, 2025)

Study on the functional role and tissue localization of GmolTrypsin in larvae of Grapholita molesta feeding on different host plants - Dongbiao Lü; Dandan Pan; Donghan Wang; Jiacheng Ye; Xiaofang Sha; Xiaoyan Zhang; Yanshen Fu; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

Canopy nitrogen and water addition affect fine-root survival strategies and carbon allocation in a warm-temperate forest in China - Wen Li; Yanzhu Su; Yiwen Qin; Fuwei Li; Tenglong Zhou; Yaqi He; Jianing Mao; Mengke Li; Chang Liu; Yifei Shi; Dandan Zhu; Chunyu Shen; et al. (Forest Ecology and Management, 2025)

Innovative nanodelivery systems for targeted breast cancer therapy: overcoming drug delivery challenges and exploring future perspectives - Dandan Su; Xiaolin Lai; Zhizhe Lin; Youfa Xu; Zhiqin Fu; Jianming Chen; Xin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Identification and functional analysis of an LTR retrotransposon insertion in CsPHYB associated with early senescence in cucumber (Cucumis sativus L.) - Hanqiang Liu; Kaihong Hu; Yuxuan Ma; Liting Fu; Zeqiang Huang; Zhihui Cheng; Yuyan Sheng; Dandan Li; Yupeng Pan (Plant Science, 2025)

Fe-doped H2TiO3 for rapid and efficient lithium extraction from shale gas wastewater - Yuchun Ren; Dandan Zhao; Chen Fu; Fei Zhou; Qian Wang; Yongsheng Fu; Tao Gong; Zhenglian Wu (Desalination, 2025)

Enhanced photosynthetic CO2 fixation in mutualistic Chlorella sp. and Mesorhizobium loti co-cultures - Dandan Yao; Yunhui Li; Kun Tian; Meng Wang; Ding Tan; Xingjia Fu; Yonghong Wu; Yun Liu; Hui Wang (Chemical Engineering Journal, 2025)

Macrogenomic and physicochemical analyses reveal microbial community and functional differences among traditional, commercial, and fortified Xiaoqu - Shaoji Zhang; Yao Lin; Tianxiang Wu; Dandan Yuan; Shoufa Jiang; Ping Fu; Wenqiang Nie (Food Bioscience, 2025)

MXene-bridged HMO/PSF adsorptive membrane for selective lithium recovery from shale gas wastewater with suppressed Mn leaching - Yuchun Ren; Dandan Zhao; Fei Zhou; Yuan Liu; Chen Fu; Yongsheng Fu; Tao Gong; Zhenglian Wu; Xinyu Yang; Zefeng Cai (Desalination, 2025)

miRNA-seq analysis revealed a potential strategy underlying poplar root responses to low nitrogen stress - Chun Wang; Tiantian Fu; Zeqi Wang; Siyu Hou; Kaijing Rong; Jing Wang; Yiyi Yin; Xiaoqian Yang; Ruen Yu; Dandan Xiao; Yanwei Wang (Planta, 2025)

In-situ gel injection of poloxamer-based metamizole provides long-acting antipyretic effects - Yueli Wang; Dongbo Li; Xiaojuan Li; Dandan Ren; Wei Zhang; Gang Shu; Juchun Lin; Haohuan Li; Funeng Xu; Guangneng Peng; Hualin Fu (Drug Delivery and Translational Research, 2025)

Associations of long-term exposure to temperature with coronary artery calcification risk among middle-aged adults: The Coronary Artery Risk Development in Young Adults (CARDIA) study - Dandan Zhao; Jie Yao; Yuanfei Li; David R. Jacobs; Yinan Zheng; Chunyu Liu; Yingbin Fu; Margaret M. Deangelis; Donald Lloyd-Jones; Lifang Hou; Kai Zhang (Science of The Total Environment, 2025)

The activation of Parageobacillus toebii in hyperthermophilic composting was depended on the bioavailability of raw materials - Shuqun Zhang; Tao Fu; Jiahuan Tang; Dandan Liu; Xincheng Zheng; Huayuan Shangguan; Hao Lin; Zhen Yu; Raymond Jianxiong Zeng (Journal of Environmental Management, 2025)

Tremendously enhanced catalytic performance of Fe(III)/peroxymonosulfate process by trace Cu(II): A high-valent metals domination in organics removal - Jieli Ou; Yiqing Liu; Linyue Zhang; Zhenran Wang; Yuqi Tang; Yongsheng Fu; Dandan Zhao (Journal of Environmental Sciences, 2025)

Extremely efficient catalytic ozonation of ammonia N to N2 using Co/Mg(OH)2 as catalysts - Tingting Cao; Jingtian Xu; Shaozhu Fu; Qinghong Zeng; Bin Cui; Han Cui; Dandan Zhou (Journal of Hazardous Materials, 2024)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

A viscoelastic wave propagation approach for dynamic backcalculation of layer properties of asphalt pavements under an impact load - Guozhi Fu; Dandan Cao; Ghim Ping Ong; Jiaqing Wang; Dong Sha (Computers and Geotechnics, 2024)

Study on the integrated technology of arsenic removal and tungsten extraction based on the formation and decomposition of arsenotungstic acid - Caifang Cao; Ailin Fu; Qiuxian Mai; Yong Li; Huaping Nie; Jian Wang; Dandan Gong; Xiaochen Qiu (Chemical Engineering Journal, 2024)

Improving ammonia oxidation to nitrogen across wide potential range via synergistic effect over Cu and Ni anchored Metal‐Organic Frameworks - Jiadian Chen; Huayu Chen; Zehao Wang; Yesheng Fu; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Ismaila Taiwo Bello; Gayi Nyongombe Ekambo; Mokhotjwa Simon Dhlamini; Da Chen (Chemical Engineering Journal, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

The transition metal composition could promote α-Fe2O3 catalytic ozonation at mild condition by improving electron transfer - Shaozhu Fu; Shuangshi Dong; Tingting Cao; Bin Cui; Jingjing Jiang; Haoran Sun; Chongjun Zhang; Dandan Zhou (Journal of Cleaner Production, 2024)

Synergistic interactions in core microbiome Rhizobiales accelerate 1,4-dioxane biodegradation - Kun Tian; Yue Zhang; Dandan Yao; Ding Tan; Xingjia Fu; Ruihuan Chen; Ming Zhong; Yuanhua Dong; Yun Liu (Journal of Hazardous Materials, 2024)

Bioinspired carbon black deposited polyimide fabric for sustainable water energy harvesting - Jianhong Guo; Leyan Zhang; Chunhua Zhang; Dandan Zhong; Weihao Long; Jieyao Qin; Zhuan Fu; Sijie Zhou; Junyao Gong; Heng Pan; Hua Ji; Lixin Du; et al. (Chemical Engineering Journal, 2024)

Novel copper-based metal–organic skeleton smart tags that respond to ammonia for real-time visual freshness monitoring of shrimp - Yongfeng Kang; Dandan Zhao; Duhong Cai; Baiyun Jia; Jianning Fu; Xiying Li; Jie Hu; Li Li (Chemical Engineering Journal, 2024)

Feasibility of intimately coupled CaO-catalytic-ozonation and bio-contact oxidation reactor for heavy metal and color removal and deep mineralization of refractory organics in actual coking wastewater - Chongjun Zhang; Shaoran Li; Haoran Sun; Shaozhu Fu; Jiang Jingjing; Han Cui; Dandan Zhou (Bioresource Technology, 2024)

Evidence for low sulfate and anoxic deep waters in early Cambrian - Yizhe Gong; Dandan Li; Menghan Li; Lilin Sun; Xiaolin Zhang; Yawen Cui; Yong Fu; Yilun Xu; Yanan Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Long-range infrared absorption spectroscopy and fast mass spectrometry for rapid online measurements of volatile organic compounds from black tea fermentation - Chongshan Yang; Leizi Jiao; Chunwang Dong; Xuelin Wen; Peng Lin; Dandan Duan; Guanglin Li; Chunjiang Zhao; Xinglan Fu; Daming Dong (Food Chemistry, 2024)

Exposure of polyethylene microplastics affects sulfur migration and transformation in anaerobic system - Yunhao Xu; Qizi Fu; Dandan He; Fan Yang; Xingyu Ma; Yan Wang; Zirui Liu; Xuran Liu; Dongbo Wang (Journal of Hazardous Materials, 2024)

Innovative multifunctional fire retardance of poly(butylene adipate-co-butylene terephthalate)-based bio-composite formulation - Qiaoqing Zhang; Jingxuan Wu; Lamei Guo; Meitong Li; Hiroshi UYAMA; Masrina Mohd Nadzir; Wen Wang; Chen Wang; Dandan Fu; Wencong Tang; Junsheng Wang; Jinjun Yang (Chemical Engineering Journal, 2024)

Prokaryotic expression, purification, and the in vitro and in vivo protection study of dehydrin WDHN2 from Triticum aestivum - Hongmei Zhang; Jiafa Wu; Dandan Fu; Min Zhang; Lunji Wang; Minggui Gong (Protoplasma, 2024)

Ectopic expression of OsWOX9A alters leaf anatomy and plant architecture in rice - Dandan Li; Longjiang Fan; Qingyao Shu; Fu Guo (Planta, 2024)

Improved physicochemical stability of fish oil nanoemulsion via a dense interfacial layer formed by hyaluronic acid-poly(glyceryl)10-stearate - Sha Ao; Xiang Luo; Hongze Wu; Yanyan Zhou; Qun Yang; Xuguang Yin; Hongliang Fu; Mengyu Huang; Dandan Lu; Kewu Zhu (Food Chemistry, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Developmental toxicity and potential mechanisms exposed to polystyrene microplastics and polybrominated diphenyl ethers during early life stages of fat greenling (Hexagrammos otakii) - Yanyan Shi; Xiaoyan Wei; Zheng Zhang; Shuai Wang; Hui Liu; Dandan Cui; Wenyuan Hua; Yanxin Fu; Yan Chen; Zhuang Xue; Xuejie Li; Wei Wang (Aquatic Toxicology, 2024)

Autotomy and Regeneration of Appendages in Crustaceans: A Review - Lei Liu; Dandan Tao; Chunlin Wang; Yuanyuan Fu; Sixiang Wang; Xinlian Huang; Wei Zhai; Weiwei Song (Journal of Ocean University of China, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Outer membrane vesicles of avian pathogenic Escherichia coli induce necroptosis and NF-κB activation in chicken macrophages via RIPK1 mediation - Zhe Li; Wenbin Shang; Ting Mei; Dandan Fu; Feng Xi; Ying Shao; Xiangjun Song; Zhenyu Wang; Kezong Qi; Jian Tu (Research in Veterinary Science, 2024)

Synergistic degradation of oxytetracycline and rhodamine B in Cu(II)/peroxymonosulfate process: Two distinct oxidation mechanisms - Jieli Ou; Yiqing Liu; Linyue Zhang; Zhenran Wang; Yuqi Tang; Yongsheng Fu; Dandan Zhao (Journal of Environmental Chemical Engineering, 2024)

Assessing the impact of low organic loading on effluent safety in wastewater treatment: Insights from an activated sludge reactor study - Chongjun Zhang; Shaoran Li; Haoran Sun; Xiaoshuang Li; Liang Fu; Chaofan Zhang; Shijun Sun; Dandan Zhou (Journal of Hazardous Materials, 2024)

Reducing infertile eggs and dead embryos during egg hatching based on respiration - Jiaojiao Wang; Rui Cao; Qiaohua Wang; Meihu Ma; Dandan Fu (Journal of Cleaner Production, 2024)

Combining microbiome and pseudotargeted metabolomics revealed the alleviative mechanism of Cupriavidus sp. WS2 on the cadmium toxicity in Vicia unijuga A.Br. - Xuefeng Yuan; Dandan Wu; Dingguo Zhang; Chunyu He; Zilong Wang; Wenqian Xu; Na Shou; Keyi Fu; Mingyuan Yue; Xin Zhang; Zunji Shi (Environmental Pollution, 2024)

How does the digital economy impact sustainable development? —An empirical study from China - Xiaoya Ma; Xiaying Feng; Dandan Fu; Jin Tong; Ming Ji (Journal of Cleaner Production, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Chronic cold environment regulates rheumatoid arthritis through modulation of gut microbiota-derived bile acids - Juan Liu; Fu Peng; Hao Cheng; Dandan Zhang; Yuxi Zhang; Lixia Wang; Fei Tang; Jing Wang; Yan Wan; Jing Wu; Yinlin Zhou; Wuwen Feng; et al. (Science of The Total Environment, 2023)

Prediction of stress-fatigue life on the impeller of the reactor coolant pump based on fluid-thermal-structure interaction method - Jiaqiong Wang; Ruizhi Wang; Rongyong Zhang; Yonggang Lu; Dandan Wang; Qiang Fu (Annals of Nuclear Energy, 2023)

Understanding the process in the removal of dimethylarsenic by a zirconium-based nanoparticle - Dandan Zhao; Chen Fu; Zhenglian Wu; Yang Yu (Colloids and Surfaces C: Environmental Aspects, 2023)

Gut microbiota bridges dietary nutrients and host immunity - Lijuan Fan; Yaoyao Xia; Youxia Wang; Dandan Han; Yanli Liu; Jiahuan Li; Jie Fu; Leli Wang; Zhending Gan; Bingnan Liu; Jian Fu; Congrui Zhu; et al. (Science China Life Sciences, 2023)

Spin state-dependent in-situ photo-Fenton-like transformation from oxygen molecule towards singlet oxygen for selective water decontamination - Jingjing Jiang; Shengda Liu; Donglong Shi; Tongze Sun; Yakun Wang; Shaozhu Fu; Yansong Liu; Mingyu Li; Dandan Zhou; Shuangshi Dong (Water Research, 2023)

Citric acid enhanced oxytetracycline degradation by Fe(Ⅲ)/peracetic acid: Performance, mechanism and influence factors - Yiqing Liu; Lin Tian; Zhenran Wang; Yongsheng Fu; Dandan Zhao (Journal of Environmental Chemical Engineering, 2023)

The epigenetic regulator Set9 harmonizes fungal development, secondary metabolism, and colonization capacity of Aspergillus flavus - Ling Hao; Mengjuan Zhang; Chi Yang; Xiaohua Pan; Dandan Wu; Hong Lin; Dongmei Ma; Yanfang Yao; Wangzhuo Fu; Jiarui Chang; Yanling Yang; Zhenhong Zhuang (International Journal of Food Microbiology, 2023)

Influence of nitrogen addition on the functional diversity and biomass of fine roots in warm-temperate and subtropical forests - Wen Li; Wenqian Wang; Ruomin Sun; Mengke Li; Haowei Liu; Yifei Shi; Dandan Zhu; Junyong Li; Lei Ma; Shenglei Fu (Forest Ecology and Management, 2023)

Spatio-temporal characteristics of meteorological drought based on the MCI of Penman–Monteith - Haixia Yu; Dandan Yang; Bingjun Liu; Jianyu Fu; Zhihao Liang (Natural Hazards, 2023)

Molecular mechanisms of caramel-like odorant-olfactory receptor interactions based on a computational chemistry approach - Shitong Zeng; Lili Zhang; Peng Li; Dandan Pu; Yingjie Fu; Ruiyi Zheng; Hui Xi; Kaina Qiao; Dingzhong Wang; Baoguo Sun; Shihao Sun; Yuyu Zhang (Food Research International, 2023)

The transcriptional regulator EtrA mediates ompW contributing to the pathogenicity of avian pathogenic Escherichia coli - Dandan Fu; Qianqian Zheng; Xiaoyan Wu; Jianmei Wu; Ying Shao; Zhenyu Wang; Jian Tu; Xiangjun Song; Kezong Qi (Veterinary Microbiology, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Lead-imprinted polyvinylidene fluoride membrane for selective removal of lead from contaminated water: material fabrication, filtration application, and mechanism study - Dandan Zhao; Chen Fu; Sudan Lin; Yongzhi Xu; Haoran He; Siyuan Liu; Xueqing Shi (Environmental Science and Pollution Research, 2023)

Sedimentary organic molecular compositions reveal the influence of glacier retreat on ecology on the Tibetan Plateau - Siwei Shi; Hai Xu; Yong Shui; Dandan Liu; Qiaorong Xie; Kang'en Zhou; Jin Zhang; Yunping Song; Jing Wang; Chukun Hu; Yuchun Wang; Pingqing Fu (Science of The Total Environment, 2023)

RETRACTED: Surfactant enhances anaerobic fermentative hydrogen sulfide production: Changes in sulfur-containing organics structure and microbial community - Xuemei Li; Qizi Fu; Wenming Wang; Xuran Liu; Dandan He; Xiaomei Jiang; Qiliang Yang; Dongbo Wang (Science of The Total Environment, 2023)

A review of filamentous sludge bulking controls from conventional methods to emerging quorum quenching strategies - Xin Lu; Ge Yan; Liang Fu; Bin Cui; Jinfeng Wang; Dandan Zhou (Water Research, 2023)

Revealing an unrecognized role of free ammonia in sulfur transformation during sludge anaerobic treatment - Qizi Fu; Sha Long; Yunhao Xu; Yan Wang; Bentao Yang; Dandan He; Xuemei Li; Xuran Liu; Qi Lu; Dongbo Wang (Journal of Hazardous Materials, 2023)

CRISPR/Cas9-mediated targeted mutagenesis of two homoeoalleles in tobacco confers resistance to powdery mildew - Wang Xuebo; Li Dandan; Tan Xiaolei; Cai Changchun; Zhang Xinyao; Shen Zhan; Yang Aiguo; Fu Xiankui; Liu Dan (Euphytica, 2023)

Novel Y2O3 based calcium-alginate beads for highly selective adsorption of phosphate from aqueous solution - Sudan Lin; Yongzhi Xu; Chen Fu; Haifeng Zhang; Qiaoping Kong; Haoran He; Siyuan Liu; Xueqing Shi; Dandan Zhao (Environmental Science and Pollution Research, 2023)

Synergistic effects of simultaneous coupling ozonation and biodegradation for coking wastewater treatment: Advances in COD removal, toxic elimination, and microbial regulation - Bin Cui; Shaozhu Fu; Xin Hao; Dandan Zhou (Chemosphere, 2023)

The p-hydroxybenzoic acid enhanced lipid accumulation of Chlorella under antibiotic stress - Huiwen Yang; Zhenhao Zhao; Yang Liu; Liang Fu; Dandan Zhou (Resources, Conservation and Recycling, 2023)

Efficient extraction approach based on polydimethylsiloxane/ZIF-derived carbons sponge followed by GC–MS for the determination of volatile compounds in cumin - Lili Wang; Jihong Fu; Xinxing Jiang; Dandan Li (Food Chemistry, 2023)

Social network of filamentous Sphaerotilus during activated sludge bulking: Identifying the roles of signaling molecules and verifying a novel control strategy - Xin Lu; Congli Chen; Liang Fu; Bin Cui; Dandan Zhou (Chemical Engineering Journal, 2023)

Ammonia fiber expansion-assisted deep eutectic solvent treatment for wheat straw fraction separation and bioconversion - Mingyang Hu; Lin Yuan; Ziyuan Cai; Weihua Zhang; Qiang Fu; Dandan Ji (Bioresource Technology, 2023)

Quantifying the associations of the air pollutant SO2 on outpatient visits for conjunctivitis in Hangzhou, China - Zhijian Chen; Qiuli Fu; Lizhi Wu; Peiwei Xu; Dandan Xu; Xuejiao Pan; Xiaoming Lou; Xiaofeng Wang; Ke Yao; Zhe Mo (Environmental Science and Pollution Research, 2022)

Iron redistribution induces oxidative burst and resistance in maize against Curvularia lunata - Dandan Fu; Jiayang Li; Xue Yang; Wenling Li; Zengran Zhou; Shuqin Xiao; Chunsheng Xue (Planta, 2022)

Photocatalysis of aqueous PFOA by common catalysts of In2O3, Ga2O3, TiO2, CeO2 and CdS: influence factors and mechanistic insights - Caixia Fu; Xiuru Xu; Chunmiao Zheng; Xinjie Liu; Dandan Zhao; Wenhui Qiu (Environmental Geochemistry and Health, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Increasing mortality caused by chronic obstructive pulmonary disease (COPD) in relation with exposure to ambient fine particulate matters: an analysis in Southeastern China - Zhijian Chen; Qiuli Fu; Guangming Mao; Lizhi Wu; Peiwei Xu; Dandan Xu; Zhifang Wang; Xuejiao Pan; Yuan Chen; Xiaoming Lou; Zhe Mo; Xiaofeng Wang; et al. (Environmental Science and Pollution Research, 2021)

Changes in soil ammonia oxidizers and potential nitrification after clear-cutting of boreal forests in China - Dandan Qi; Fujuan Feng; Yanmei Fu; Xue Sun (World Journal of Microbiology and Biotechnology, 2021)

Analysis of exploitation control in typical groundwater over-exploited area in North China Plain - Kairan Wang; Huawei Chen; Shidong Fu; Fulin Li; Zhen Wu; Dandan Xu (Hydrological Sciences Journal, 2021)

Phenotypic characteristics of ramie (Boehmeria nivea L) germplasm resources based on UAV remote sensing - Dandan Cui; Guoxian Cui; Ruifang Yang; Wei She; Yaoduan Liu; Hui Wang; Xiaohui Su; Jilong Wang; Wanhui Liu; Xinhui Wang; Jieyi Liu; Hongyu Fu (Genetic Resources and Crop Evolution, 2021)

The key iron assimilation genes ClFTR1 , ClNPS6 were crucial for virulence of Curvularia lunata via initiating its appressorium formation and virulence factors - Yuanyuan Lu; Jiaying Sun; Yibo Gao; Kexin Liu; Mingyue Yuan; Weida Gao; Fen Wang; Dandan Fu; Nan Chen; Shuqin Xiao; Chunsheng Xue (Environmental Microbiology, 2021)
Summary Iron is virtually an essential nutrient for all organisms, to understand how iron contributes to virulence of plant pathogenic fungi, we identified ClFTR1 and ClNPS6 in maize pathogen Curvularia lunata ( Cochliobolus lunatus ) in this study. Disruption of ClNPS6 significantly impaired siderophore biosynthesis. ClFTR1 and ClNPS6 did mediate oxidative stress but had no significant impact on vegetative growth, conidiation, cell wall integrity and sexual reproduction. Conidial germination delayed and appressoria formation reduced in Δ Clftr1 comparing with wild type (WT) CX‐3. Genes responsible for conidial germination, appressoria formation, non‐host selective toxin biosynthesis and cell wall degrading enzymes were also downregulated in the transcriptome of Δ Clftr1 and Δ Clnps6 compared with WT. The conidial development, toxin biosynthesis and polygalacturonase activity were impaired in the mutant strains with ClFTR1 and ClNPS6 deletion during their infection to maize. ClFTR1 and ClNPS6 were upregulated expression at 12–24 and 48–120 hpi in WT respectively. ClFTR1 positively regulated conidial germination, appressoria formation in the biotrophy‐specific phase. ClNPS6 positively regulates non‐host selective toxin biosynthesis and cell wall degrading enzyme activity in the necrotrophy‐specific phase. Our results indicated that ClFTR1 and ClNPS6 were key genes of pathogen known to conidia development and virulence factors.

Simulation of Evapotranspiration Based on BEPS-TerrainLab V2.0 from 1990 to 2018 in the Dajiuhu Basin - Zongfan Wu; Lihua Zhang; Dandan Liu; Kang Zhang; Zhiru Zhu; Yasheng Fu; Yongming Ma (Chinese Geographical Science, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Phosphorus supply via a fed-batch strategy improves lipid heterotrophic production of Chlorella regularis - Liang Fu; Ge Yan; Yunbao Li; Qingcheng Li; Dandan Zhou (Environmental Science and Pollution Research, 2020)

Characterization of viromes within mosquito species in China - Jiang Du; Fan Li; Yelin Han; Shihong Fu; Bo Liu; Nan Shao; Haoxiang Su; Weijia Zhang; Dandan Zheng; Wenwen Lei; Jie Dong; Lilian Sun; et al. (Science China Life Sciences, 2020)

Non-coding RNAs and transposable elements in plant genomes: emergence, regulatory mechanisms and roles in plant development and stress responses - Jinna Hou; Dandan Lu; Annaliese S. Mason; Baoquan Li; Meili Xiao; Sufang An; Donghui Fu (Planta, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Evoked potential study of the inferior collicular response to constant frequency-frequency modulation (CF-FM) sounds in FM and CF-FM bats - Ziying Fu; Na Xu; Guimin Zhang; Dandan Zhou; Long Liu; Jia Tang; Philip Hung-Sun Jen; Qicai Chen (Journal of Comparative Physiology A, 2019)

Contrasting roles of phenol and pyrocatechol on the degradation of 4-chlorophenol in a photocatalytic–biological reactor - Chaofan Zhang; Liang Fu; Zhengxue Xu; Houfeng Xiong; Dandan Zhou; Mingxin Huo (Environmental Science and Pollution Research, 2017)

Alantolactone induces G1 phase arrest and apoptosis of multiple myeloma cells and overcomes bortezomib resistance - Yao Yao; Dandan Xia; Yueping Bian; Yueyue Sun; Feng Zhu; Bin Pan; Mingshan Niu; Kai Zhao; Qingyun Wu; Jianlin Qiao; Chunling Fu; Zhenyu Li; et al. (Apoptosis, 2015)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Constructing a dense genetic linkage map and mapping QTL for the traits of flower development in Brassica carinata - Jun Zou; Harsh Raman; Shaomin Guo; Dandan Hu; Zili Wei; Ziliang Luo; Yan Long; Wenxia Shi; Zhong Fu; Dezhi Du; Jinling Meng (Theoretical and Applied Genetics, 2014)

Cloning, Expression, and Characterization of an GHF 11 Xylanase from Aspergillus niger XZ-3S - Guanhua Fu; Yongtao Wang; Dandan Wang; Chenyan Zhou (Indian Journal of Microbiology, 2012)

Foraging responses of clonal plants to multi-patch environmental heterogeneity: spatial preference and temporal reversibility - Ying Gao; Fu Xing; Yongjun Jin; Dandan Nie; Ying Wang (Plant and Soil, 2012)

Improved LASSO priors for shrinkage quantitative trait loci mapping - Ming Fang; Dan Jiang; Dandan Li; Runqing Yang; Weixuan Fu; Lijun Pu; Huijiang Gao; Guihua Wang; Liyun Yu (Theoretical and Applied Genetics, 2012)

DJ-1 may contribute to metastasis of non-small cell lung cancer - Jing Bai; Changlong Guo; Wenjing Sun; Ming Li; Xiangning Meng; Yang Yu; Yan Jin; Dandan Tong; Jingshu Geng; Qi Huang; Jiping Qi; Songbin Fu (Molecular Biology Reports, 2012)